Left Bundle Pacing for Left Bundle Branch Block and Intermittent Third-Degree Atrioventricular Block in a MYH7 Mutation-Related Hypertrophic Cardiomyopathy With Restrictive Phenotype in a Child - Zhang, Luyan; Cheng, Xueying; Chen, Jinlong; Zhou, Ming; Qian, Tianwei; Zhang, Zhongman; Yin, Jie; Zhang, Han; Dai, Genyin; Qin, Yuming; Yang, Shiwei (Frontiers in Pediatrics, 2020)
Hypertrophic cardiomyopathy (HCM) is a group of myocardial diseases defined by cardiac hypertrophy which cannot be explained by secondary causes with a non-dilated left ventricle and preserved or increased ejection fraction. Sometimes it can be combined with restrictive cardiomyopathy. Here we describe a very rare case of a 12-year-old girl with non-obstructive hypertrophic cardiomyopathy accompanied by restrictive phenotype, complete left bundle branch block and intermittent third-degree atrioventricular block, who presented with recurrent syncope. Her father was also found to have hypertrophic cardiomyopathy and treated with implantable cardioverter defibrillator for ventricular tachycardia. Her younger brother is currently asymptomatic but echocardiogram showed hypertrophic cardiomyopathy. Genetic analysis identified a heterozygous missense mutation (c.2155C>T, p.R719W) of MYH7 in the proband girl, her father and her brother. The girl was treated with left bundle pacing and recovered well. The case we present further demonstrates the feasibility of left bundle pacing in children.